Structural Model of AI-Based Feedback's Impact on Employee Commitment and Creativity to Enhance Organizational Innovation - Mari Maryati; Tatang Supriyadi (Almana : Jurnal Manajemen dan Bisnis, 2026)
The increasing use of artificial intelligence (AI) in workplace feedback systems has reshaped how employees receive performance evaluations and guidance. While AI promises efficiency and objectivity, its influence on employees’ psychological engagement, creative behavior, and organizational innovation is not yet fully understood. This study aims to examine how AI-based feedback affects employees’ work commitment and creativity and how these factors, in turn, contribute to organizational innovation. A quantitative explanatory approach was employed, using survey data collected from employees who had experienced AI-supported feedback in their organizations. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that AI-based feedback positively influences both work commitment and employee creativity. In addition, work commitment and creativity each play a significant role in promoting organizational innovation and jointly mediate the relationship between AI-based feedback and innovation outcomes. These results suggest that AI-based feedback does not automatically lead to innovation; instead, its benefits emerge when the technology strengthens employees’ emotional attachment to their work and supports creative exploration. In conclusion, this study highlights the importance of designing AI-based feedback systems that are transparent, supportive, and development-oriented in order to fully realize their potential in fostering sustainable organizational innovation.